2021
DOI: 10.1192/j.eurpsy.2021.21
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences on externalizing psychopathology overlap with cognitive functioning and show developmental variation

Abstract: Background Questions remain regarding whether genetic influences on early life psychopathology overlap with cognition and show developmental variation. Methods Using data from 9,421 individuals aged 8 to 21 from the Philadelphia Neurodevelopmental Cohort, factors of psychopathology were generated using a bifactor model of item-level data from a psychiatric interview. Five orthogonal factors were generated: anxious-misery (mood and anxiety), externalizing (attention deficit hyperactivity and conduct disorder), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 84 publications
(138 reference statements)
0
3
0
Order By: Relevance
“…Twin studies have also supported the view that comorbidity among the specific disorders can be ascribed to a common genetic liability (Bornovalova et al., 2010 ; Tuvblad, Zheng, Raine, & Baker, 2009 ). Heritability estimates based on common single nucleotide polymorphisms (SNPs) are somewhat inconsistent across studies, ranging between 5% and 46% (Cheesman et al., 2017 ; Karlsson Linnér et al., 2021 ; Mollon et al., 2021 ; Pappa et al., 2015 ). Although genetic variation appears to play an important contribution to individual differences, little is known about the biology underlying externalizing problems (Barr & Dick, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Twin studies have also supported the view that comorbidity among the specific disorders can be ascribed to a common genetic liability (Bornovalova et al., 2010 ; Tuvblad, Zheng, Raine, & Baker, 2009 ). Heritability estimates based on common single nucleotide polymorphisms (SNPs) are somewhat inconsistent across studies, ranging between 5% and 46% (Cheesman et al., 2017 ; Karlsson Linnér et al., 2021 ; Mollon et al., 2021 ; Pappa et al., 2015 ). Although genetic variation appears to play an important contribution to individual differences, little is known about the biology underlying externalizing problems (Barr & Dick, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This general domain explains most of the associations with positive attributes, which suggests this association is not due to a particular set of symptoms, but to overall mental health problems which are shared among all symptomatic domains. After parsing out variance due to this common factor, the conduct score still explained additional variability in positive attributes, which suggests the associations between conducts specific factor and positive attributes might be due to other mechanisms not shared with the common factors such as genetic overlap with poor verbal and spatial reasoning, verbal knowledge, and general cognitive ability [40], for example. Previous research has found bidirectional associations between positive attributes and both internalizing and externalizing disorders, especially the latter [11].…”
Section: Discussionmentioning
confidence: 99%
“…As recently pointed out by Arango et al ( 13 ), transdiagnostic risk/protective factors—such as childhood adversities, stressful events, being second generation immigrant—are mostly involved in the early neurodevelopmental period ( 14 ). The evidence is rapidly growing on the interaction between gene-by-environment-by-time of exposure, highlighting that environmental factors underly much of the variation in clinical and neurobiological phenotypes of mental disorders and their outcomes ( 15 , 16 ).…”
mentioning
confidence: 99%